Financing For Development : Revisiting the Monterrey Consensus. (Policy Papers; Policy Paper ;, 2015)
2015 is set to be a pivotal year for the international development agenda, with agreements to be reached on the objectives and policies for promoting development that is economically, socially, and environmentally sustainable through 2030. The first stage in completing the debate on these issues is the Third UN Conference on Financing for Development (FfD), to be held in Addis Ababa during July 13-16, 2015, which aims to build an international consensus on the actions needed to ensure that sufficient financing is available for developing countries in pursuing sustainable development.